Biomarkers of carcinogenesis and tumour growth in patients with cutaneous melanoma and obstructive sleep apnoea. Issue 3 (15th March 2018) - Santamaria-Martos, Fernando; Benítez, Ivan; Girón, Cristina; Barbé, Ferran; Martínez-García, Miguel-Angel; Hernández, Luis; Montserrat, Josep M.; Nagore, Eduardo; Martorell, Antonio; Campos-Rodriguez, Francisco; Corral, Jaime; Cabriada, Valentin; et al.
The goal of this study was to assess the relationship between the severity of obstructive sleep apnoea (OSA) and the levels of carcinogenesis- and tumour growth-related biomarkers in patients with cutaneous melanoma. This multicentre observational study included patients who were newly diagnosed with melanoma. The patients were classified as non-OSA (apnoea–hypopnoea index (AHI) 0–5 events·h −1 ), mild OSA (AHI 5–15 events·h −1 ) and moderate–severe OSA (AHI >15 events·h −1 ). ELISAs were performed to analyse the serum levels of hypoxia- and tumour adhesion-related biomarkers (vascular endothelial growth factor (VEGF), interleukin (IL)-8, intracellular adhesion molecule (ICAM) and vascular cell adhesion molecule (VCAM)-1) and markers of tumour aggressiveness (S100 calcium-binding protein B (S100B) and melanoma inhibitory activity (MIA)). A logistic model adjusted for age, sex and body mass index was fitted to each biomarker, and the AHI served as the dependent variable. 360 patients were included (52.2% male, median (interquartile range) age 55.5 (43.8–68.0) years and AHI 8.55 (2.8–19.5) events·h −1 ). The levels of VEGF, IL-8, ICAM-1, S100B and MIA were not related to the severity of OSA. The levels of VCAM-1 were higher in patients with OSA than those without OSA (mild OSA: odds ratio (OR) 2.07, p=0.021; moderate–severe OSA: OR 2.35, p=0.013). In patients with cutaneous melanoma, OSA was associated with elevated circulating levels of VCAM-1 that could indicate the contribution of OSA in tumorigenesis via integrin-based adhesion. In patients with cutaneous melanoma, OSA is associated with increased expression of a biomarker of tumorigenesis http://ow.ly/mLo430i9Z8j